Effects of a variable light intensity lighting program on the welfare and performance of commercial broiler chickens - Kang, Seong W.; Christensen, Karen D.; Kidd Jr, Michael T.; Orlowski, Sara K.; Clark, James (Frontiers in Physiology, 2023)
To evaluate the effects of variable light (VL) intensity lighting program on performance and welfare of broilers, four commercial trials were conducted for behaviors, mortality, leg-health, performance, and brain welfare indicator genes including tryptophan hydroxylase 2 (TPH2) and tyrosine hydroxylase (TH), glucocorticoid receptor (GR), brain-derived neurotropic factor (BDNF), and melanopsin (Opn4) gene expression. Day old broilers were housed in four commercial broiler houses. Each quadrant (section) of the house was placed with 4,800 chicks. Four lighting programs began on day 7 with 5 lux (lx), 20 lx, natural light (NL, 480 lx), and VL (2-5/40 lx) using LED lights on a 16L:8D photoperiod. In VL house, number of dustbathing holes was significantly higher compared to those of NL houses as well as 5 lx and 20 lx houses. Daily physical activity, footpad condition, fear response to novel object, body weight, feed conversion ratio (FCR), and number of leg-health induced culled birds were affected by VL intensity lighting program. Expressions of TPH2 in the DRN and VTA of VL birds were lower compared to 5 lx and 20 lx birds on day 42 (p<0.05). Higher expression of VTA-TH in 5 lx birds than those of 20L, NL and VL birds suggests the high stress-susceptibility of 5 lx birds. Lower VTA-GR expression in 20 lx and VL birds indicates low stress in birds compared to NL and 5 lx birds (p<0.05). VTA-BDNF expression of NL birds was 2.5 fold higher than those of 5 lx, 20 lx and VL birds (p<0.05), and VL birds showed the lowest level of BDNF expression (p<0.05), suggesting the chronic social defeat stress in NL birds. Result of VTA-Opn4 expression on day 42 suggests the possible role of VTA-Opn4 on broilers welfare through central light perception. Taken together, VL intensity lighting program increased volunteer natural behaviors and physical activity, which may improve footpad condition and leg-health of birds, consequently. Performance data including the increased daily weight gain and the lowered FCR, and results of brain welfare indicator gene expression showed the beneficial effect of VL intensity lighting program on performance and welfare of commercial broilers.